Safety and Efficacy of Subcutaneous Daratumumab in Systemic AL Amyloidosis - Hughes MS; Lentzsch S (Dove Medical Press, 2023)
Michael Sang Hughes, Suzanne Lentzsch Department of Hematology-Oncology, Columbia University Irving Medical Center, New York, NY, USACorrespondence: Suzanne Lentzsch, Department of Hematology-Oncology, Columbia University Irving Medical Center, MH-6GN 435, 161 Fort Washington Ave, New York, NY, 10032, USA, Tel +1 212-305-5098, Email sl3440@cumc.columbia.eduIntroduction: Systemic AL amyloidosis, a plasma cell dyscrasia, is characterized by the production of misfolded immunoglobulin light chain. These misfolded proteins aggregate into amyloid fibrils and deposit throughout the body, resulting in widespread organ dysfunction and ultimately death. Achieving rapid and maximal elimination of the plasma cell clone is crucial to long-term survival. Daratumumab, an anti-CD38 monoclonal antibody delivered intravenously, has been swiftly incorporated into standard first-line treatment regimens. A novel formulation of daratumumab has been developed that can be injected subcutaneously.Areas Covered: As a retrospective qualitative review of prior publications involving daratumumab, this work briefly summarizes the existing data regarding the safety and efficacy of subcutaneous (SC) daratumumab, compared to intravenous (IV) daratumumab. SC daratumumab appears to deliver the same disease benefit as IV daratumumab to patients with decreased infusion-related reactions (IRRs), decreased time for administration, and similar rates of adverse events (AEs) intrinsically related to daratumumab.Expert Opinion: SC daratumumab is preferred over IV daratumumab, but the clinical situation ultimately should determine route of administration. Further investigation into cost-effectiveness benefit is warranted. Keywords: plasma cell dyscrasia, daratumumab, AL amyloidosis, adverse events, AE